Răspuns :
a+b=25
25-(a-b)=14 => a-b=25-14=11 => a=11+b
si din amandoua rezulta ca 11+b+b=25 => 2b=14 => b=7 => a=18
25-(a-b)=14 => a-b=25-14=11 => a=11+b
si din amandoua rezulta ca 11+b+b=25 => 2b=14 => b=7 => a=18
a + b = 25
(a + b) - (a - b) = 14
25 - (a - b) = 14
- (a - b) = - 25 + 14
a - b = 11
a + b = 25
le adunam
2a = 36
a = 36 : 2
a = 18
b = 25 - 18
b = 7
si
b + a = 25
(b + a) - (b - a) = 14
25 - (b - a) = 14
- (b - a) = - 25 + 14
b - a = 11
b + a = 25
2b = 36
b = 18
a = 25 - 18
a = 7
(a + b) - (a - b) = 14
25 - (a - b) = 14
- (a - b) = - 25 + 14
a - b = 11
a + b = 25
le adunam
2a = 36
a = 36 : 2
a = 18
b = 25 - 18
b = 7
si
b + a = 25
(b + a) - (b - a) = 14
25 - (b - a) = 14
- (b - a) = - 25 + 14
b - a = 11
b + a = 25
2b = 36
b = 18
a = 25 - 18
a = 7